Depositional environment and diagenetic development of the Mauddud Formation in wells Am-3, WQ-3, southern Iraq - Yehva, Rafah (Iraqi Journal of Science, 2025)
The Mauddud Formation of Southern Iraq was deposited within four subenvironments, shallow restricted marine, shoal, open marine, and deep marine environments in a slowely subsiding ramp setting. The eustatic sea level changes was the main controlling factor on the position of different diagenetle environments. The basinward shift of the meteoric lense during the late highstand of each cycle caused intensive cementation of the transgressive deep and open marine fades where as the zone affected by mixing dolomitization was the result of the shoreward shift of the mixing zone after the subsequent major transgression.